2021
DOI: 10.1186/s13019-021-01639-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal and climate variations on in-hospital mortality and length of stay in patients with type A aortic dissection

Abstract: Objective To investigate the effects of seasonal and climatic changes on postoperative in-hospital mortality and length of stay (LOS) in patients with type A acute aortic dissection (AAD). Methods Patients undergoing implantation of the modified triple-branched stent graft to replace the descending aorta in addition to aortic root reconstruction for type A AAD in our hospital from January 2016 to December 2019 were included. Relevant data were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A previous study has shown that the onset of TAAD in autumn may be a factor that raises in-hospital mortality ( 10 ). Luo et al found that patients admitted in autumn had an increased risk of in-hospital death following surgery for TAAD ( 11 ). However, previous scholarship failed to establish the contrast between the outcomes of TEVAR operated in spring and autumn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has shown that the onset of TAAD in autumn may be a factor that raises in-hospital mortality ( 10 ). Luo et al found that patients admitted in autumn had an increased risk of in-hospital death following surgery for TAAD ( 11 ). However, previous scholarship failed to establish the contrast between the outcomes of TEVAR operated in spring and autumn.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms are as follows: In contrast to previous studies ( 10 , 11 ), patients with TAAD usually require open surgery, and a warmer climate after surgery is critical for massive invasive healing ( 11 ). Therefore, autumn is more dangerous for TAAD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 1970s to the present, the proportion of ATAAD surgery combined with CAD has been high (20~30%) [ 21 ], while that combined with CABG is not high (5.6~7.5%) [ 22 ], and many articles indicate that CABG increases mortality [ 23 , 24 ]. Therefore, exploring new surgical strategies to improve the prognosis of ATAAD combined with CAD is clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a life-threatening disease with a prevalence of about 6 cases per 100000 person-years in a large population (3). The accidence rate of aortic dissection is estimated to rise due to circadian and seasonal variation (4,5). In addition, multiple risk factors were involved in AD development, including hypertension(6), male gender, and an average age of around 70 (7).…”
Section: Introductionmentioning
confidence: 99%